Thanks for your help.... How about this one? Using the definition of derivate find f ` (x) f(x) = x/(2x-1) f ` (x) = lim h->0 [(f(x+h)) – (f(x))]/h lim h->0 ([((x+h) / (2x+2h-1))-(x/(2x-1))]/h) . [((2x+2h-1)(2x-1)) / ((2x+2h-1)(2x-1))] lim h->0 [(2x^2)-x+(2xh)-h-(2x^2)-(2hx)+x]/(h(2x+2h-1)(2x-1)) lim h->0 -h/(h(2x+2h-1)(2x-1)) = -1/(2x-1)^2
just a suggestion, ladyrae: if you have more questions on this, don't open any new thread, continue to use this instead. In addition, try to learn LATEX formatting, it's not very difficult..